Hip fracture systems—European experience. Issue 1 (March 2020) - Chesser, Tim J.S.; Inman, Dominic; Johansen, Antony; Belluati, Alberto; Pari, Carlotta; Contini, Achille; Voeten, Stijn.C.; Hegeman, Johannes H.; Ponsen, Kornelis J.; Montero-Fernández, Nuria; Delgado-Martínez, Alberto; Chana-Rodríguez, Francisco
Abstract : Abstract: European countries have established health care systems but are struggling with the increasing rise of fragility fractures in their aging population. In trying to address this significant burden, countries are establishing national guidelines and standards, focusing on hip fractures, which represent the significant cost for this patient group. This has evolved with the establishment of national audits and guidelines. Reports from 4 European countries (England, Italy, Netherlands, and Spain) are presented. All nations have identified both deficiencies in their systems, and protocols to improve these deficiences. When standards are introduced, there has been evidence of improved results. Significantly more work is needed to understand the key components of the systems and pathways, and efforts to study and standardize care are ongoing.